Hak Kemerdekaan Mengeluarkan Pendapat bagi Wartawan melalui Media Massa - Anita Marianche (Badan Strategi Kebijakan Hukum, 2012)
Freedom of the press is a manifestation of popular sovereignty set forth in Section 28F of the 1945 Constitution and becomes a very important element in creating a democractic life of society, nation and state which includes activities to search, to acquire, to possess, to keep, to process and to convey information. Freedom of the press guaranteed by the state through legislation including guarding the independence of national integrity, upholding religious values, truth, justice, morality, ethics, promotes social and intellectual life of the nation. Freedom of the press still faces many problems, especially with the increasing cases of physical violence against journalists and non-physical in journalistic activities. On the other hand, freedom of the press who do not abide the code of conduct and regulations can be abused for the benefit of a particular group or class. Violation of journalistic ethics by journalists in the name of democracy, and even tend to ignore the rules of professionalism. Data collection techniques performed in this evaluation using interviews, questionnaires and documents.The research approach used in this evaluation is through qualitative and quantitative approaches. Data obtained from th evaluation, collected, processed and analyzed quantitatively and qualitatively to describe, illustrate and to explain the problem of evaluation. The evaluation program is also expected to identify constraints either administrative, procedural and quality associated with the protection of the right to freedom of expression for journalists in the mass media and the settlement of code of ethics violations committed by journalists to the decline the level of violence experienced by journalists, and also reduced violations of the code of ethics by journalists in performig its duties.